Probing the electronic relaxation pathways and photostability of the synthetic nucleobase Z via laser interfaced mass spectrometry. Issue 45 (10th November 2022) - Whitaker, William; Moncrieff, Katya E.; Anstöter, Cate S.; Wong, Natalie G. K.; Berenbeim, Jacob A.; Dessent, Caroline E. H.
Abstract : The photostability of synthetic (unnatural) nucleobases is important in establishing the integrity of new genetic alphabets, and critical for developing healthy semisynthetic organisms. Abstract : The photostability of synthetic (unnatural) nucleobases is important in establishing the integrity of new genetic alphabets, and critical for developing healthy semisynthetic organisms. Here, we report the first study to explore the photostability and electronic decay pathways of the synthetic nucleobase, Z (6-amino-5-nitro-2(1 H )-pyridone), combining UV laser photodissociation and collisional dissociation measurements to characterise the decay pathways across the region from 3.1–4.9 eV. Photoexcitation across this region produced the m / z 138 ion as the dominant photofragment, mirroring the dominant fragment produced upon higher-energy collisional excitation. Analysis of the ion-yield production curve profile for the m / z 138 ion indicates that it is produced following ultrafast excited state decay with boil off of the OH functional group of Z from the hot electronic ground state. Electronic structure calculations provide physical insight into why this is the dominant fragmentation pathway, since a node in the electron density along the C–OH bond is found for all tautomers of Z. While the dominant decay pathway for Z is consistent with ultrafast excited state decay, we also identify several minor dissociative photochemistry decay pathways, associated with intrinsic photoinstability. The results presented here can be used to guide the development of more photostable synthetic nucleobases.